The Burden of ‘White’ Sugar: Producing and Consuming Whiteness in Australia - Affeldt, Stefanie (Studia Anglica Posnaniensia, 2017)
This article investigates the history of the Queensland cane sugar industry and its cultural and political relations. It explores the way the sugar industry was transformed from an enterprise drawing on the traditional plantation crop cultivated by an unfree labour force and employing workers into an industry that was an important, symbolical element of ‘White Australia’ that was firmly grounded in the cultural, political, nationalist, and racist reasoning of the day. The demographic and social changes drew their incitement and legitimation from the ‘White Australia’ culture that was represented in all social strata. Australia was geographically remote but culturally close to the mother country and was assigned a special position as a lone outpost of Western culture. This was aggravated by scenarios of allegedly imminent invasions by the surrounding Asian powers, which further urged cane sugar’s transformation from a ‘black’ to a ‘white man’s industry’. As a result, during the sugar strikes of the early 20th century, the white Australian sugar workers were able to emphasize their ‘whiteness’ to press for improvements in wages and working conditions. Despite being a matter of constant discussion, the public acceptance of the ‘white sugar campaign’ was reflected by the high consumption of sugar. Moreover, the industry was lauded for its global uniqueness and its significance to the Australian nation. Eventually, the ‘burden’ of ‘white sugar’ was a monetary, but even more so moral support of an industry that was supposed to provide a solution to population politics, support the national defence, and symbolize the technological advancement and durability of the ‘white race’ in a time of crisis.